THE COMPARISON OF STUDENTS’ WRITING DESCRPTIVE TEXT ABILITY BY USING JIGSAW AND SCAFFOLDING TECHNIQUE IN EVEN SEMESTER AT GRADE X STATE SENIOR HIGH SCHOOL 1 SEPUTIH RAMAN ACADEMIC YEAR 2012/2013 - Ni Putu Ayu Dian Anggraeni; Dedi Turmudi (Premise: Journal of English Education and Applied Linguistics, 2013)
Writing as one of the four skills has always been as a part of the syllabus in teaching of English. The techniques presented as a solution in this research about writing ability are Jigsaw and Scaffolding technique. There are three problems of the study, (1) Is Jigsaw technique effective to improve students’ writing descriptive text ability? (2) Is Scaffolding technique effective to improve students’ writing descriptive text ability? (3) Is there any significant difference of students’ writing descriptive text ability by using Jigsaw and Scaffolding technique? The objective of this research is (1) To know whether Jigsaw technique is effective to improve students’ writing descriptive text ability. (2) To know whether Scaffolding technique is effective to improve students’ writing descriptive text ability. (3) To know whether there is any significant difference of students’ writing descriptive text ability by using Jigsaw and Scaffolding technique. The method of investigation is held through quantitative experimental research. The researchers uses modified pretest-posttest control group design. In this experiment, the employees control group pre test post test design. The researchers is conducted at the grade X of State Senior High School 1 Seputih Raman in academic year 2012/2013. The popolation in this research is 210 students. It is consist 7 classes and each class consist 30. The researchers takes 90 students from total population as the sample. 30 students as experiment class of Jigsaw, 30 students as experiment class of Scaffolding, and 30 as control class that matching based on classification of student level. And the researchers use cluster random sampling as technique sampling. To analyze data, the researchers uses One Way ANOVA. The researchers got the result of Ft 1% = 7.31 and Ft 5% = 4.08 and it seems that FO > Ft  1% and Ft  5% in which FO = 7.31 > Ft  1% = 7.31 and Ft  5% = 4.08. The criteria of One Way ANOVA is FO ≥ Ft 1%, Ha is accepted. So, there is any difference result of students’ writing ability using Jigsaw and Scaffolding technique. Jigsaw technique is more effective than Scaffolding technique toward students writing descriptive text ability at the grade X of State Senior High School 1 Seputih Raman academic year 2012/2013. The suggestions are to raise the students’ writing descriptive text ability, it uses Jigsaw technique in writing instruction. The students must be fun and enjoy in using Jigsaw technique.